Chemical Composition of Pistacia lentiscus Seeds’ Oil from Moroccan High Atlas Mountain - Brahim Ait Mohand; Abderraouf El Antari; Fatiha Benkhalti (Journal of Food Quality)
Pistacia lentiscus is an aromatic member of the Anacardiaceae family, endemic to the Mediterranean regions, which produces red and black oleaginous seeds in maturity. Our study focuses on the characterization of Pistacia lentiscus seed oils from three localities of High Atlas Mountain in the Azilal region of Morocco. Our results showed a very appreciable oil yield reaching more than 21% which clearly differs between the three sites studied (21.33 ± 0.17% in Boizoghrane, 15.22 ± 0.10% in Tighanimine, and 7.67 ± 0.29% in Tawjanizm locality); the analysis of the total fatty acids composition revealed a predominance of the unsaturated fatty acids represented essentially by the oleic and linoleic fatty acids, and also the triglyceride composition was dominated mainly by POO + SOL, POL + SLL + PoOP, and OOO. This potential of the chemical composition offers the possibility of producing nutraceutical oil, which represents a source of income capable of insisting vulnerable local populations to protect this species from deforestation, thus maintaining biodiversity, and to reduce by this interest the migratory flow from marginal areas.